Length‐independent telomere damage drives post‐mitotic cardiomyocyte senescence. (8th February 2019) - Anderson, Rhys; Lagnado, Anthony; Maggiorani, Damien; Walaszczyk, Anna; Dookun, Emily; Chapman, James; Birch, Jodie; Salmonowicz, Hanna; Ogrodnik, Mikolaj; Jurk, Diana; Proctor, Carole; Correia‐Melo, Clara; et al.
Abstract: Ageing is the biggest risk factor for cardiovascular disease. Cellular senescence, a process driven in part by telomere shortening, has been implicated in age‐related tissue dysfunction. Here, we address the question of how senescence is induced in rarely dividing/post‐mitotic cardiomyocytes and investigate whether clearance of senescent cells attenuates age‐related cardiac dysfunction. During ageing, human and murine cardiomyocytes acquire a senescent‐like phenotype characterised by persistent DNA damage at telomere regions that can be driven by mitochondrial dysfunction and crucially can occur independently of cell division and telomere length. Length‐independent telomere damage in cardiomyocytes activates the classical senescence‐inducing pathways, p21 CIP and p16 INK4a, and results in a non‐canonical senescence‐associated secretory phenotype, which is pro‐fibrotic and pro‐hypertrophic. Pharmacological or genetic clearance of senescent cells in mice alleviates detrimental features of cardiac ageing, including myocardial hypertrophy and fibrosis. Our data describe a mechanism by which senescence can occur and contribute to age‐related myocardial dysfunction and in the wider setting to ageing in post‐mitotic tissues. Synopsis: Cellular senescence induced by telomere shortening during cell division has been implicated in age‐related tissue dysfunction. In rarely dividing post‐mitotic cells, telomeric DNA damage leading to senescence is triggered by mitochondria‐derived reactive oxygen species (ROS), suggesting new avenues for improved cardiac regeneration therapies. Length‐independent telomere damage occurs in ageing post‐mitotic cardiomyocytes. Mitochondrial dysfunction and ROS drive telomere dysfunction in aged cardiomyocytes. Senescent cell clearance reduces hypertrophy and fibrosis in aged hearts. The heart responds to senescent cell clearance with limited cardiomyocyte regeneration. Abstract : Mitochondria derived reactive oxygen species trigger persistent DNA damage at telomeres, cardiomyocyte senescence and heart dysfunction during ageing.